Retinoic Acid Signaling in B Cells Is Required for the Generation of an Effective T-Independent Immune Response - Marks, Ellen; Ortiz, Carla; Pantazi, Eirini; Bailey, Charlotte S.; Lord, Graham M.; Waldschmidt, Thomas J.; Noelle, Randolph J.; Elgueta, Raul (Frontiers in Immunology, 2016)
Retinoic acid (RA) plays an important role in the balance of inflammation and tolerance in T cells. Furthermore, it has been demonstrated that RA facilitates IgA isotype switching in B cells in vivo. However, it is unclear whether RA has a direct effect on T-independent B cell responses in vivo. To address this question, we generated a mouse model where RA signalling in the B cell lineage is specifically silenced. This was achieved through the overexpression of a dominant negative receptor for RA (dnRAR) in the B cell lineage. In this model, we found a dramatic reduction in marginal zone B cells and accumulation of transitional 2 B cells in the spleen. We also observed a reduction in B1 B cells in the peritoneum with a defect in the T-independent B cell response against 2,4,6-trinitrophenyl (TNP). This was not a result of inhibited development of B cells in the bone marrow but likely the result of both, defective expression of S1P1 in MZ B cells and a defect in the development of MZ and B1 B cells. This suggests that RAR expression in B cells is important for the B cell frequency in the marginal zone and peritoneum to generate an efficient T-independent humoral response.